Competing endogenous RNA networks of CYP4Z1 and pseudogene CYP4Z2P confer tamoxifen resistance in breast cancer. (15th May 2016) - Zheng, Lufeng; Li, Xiaoman; Meng, Xia; Chou, Jinjiang; Hu, Jinhang; Zhang, Feng; Zhang, Zhiting; Xing, Yingying; Liu, Yu; Xi, Tao
Abstract: Patients with estrogen receptor α (ERα)-positive breast cancer can be treated with endocrine therapy using anti-estrogens such as tamoxifen; nonetheless, patients often develop resistance limiting the success of breast cancer treatment. The potential mechanisms remain elusive. In detail, many miRNAs have been associated with breast cancer tamoxifen resistance, but no studies have addressed the role of miRNA-mediated competitive endogenous RNAs network (ceRNET) in tamoxifen resistance. The ceRNET between CYP4Z1 and pseudogene CYP4Z2P has been revealed to promote breast cancer angiogenesis. However, its function in tamoxifen resistance remains unclear. Here we report CYP4Z1 and CYP4Z2P were downregulated in MCF-7 cells compared with tamoxifen-resistant MCF-7-TamR cells. Enforced upregulation of CYP4Z1- or CYP4Z2P-3′UTR level renders MCF-7 Cells resistant to tamoxifen. We find that overexpression of CYP4Z1- or CYP4Z2P-3′UTR enhances the transcriptional activity of ERα through the activation of ERα phosphorylation. Furthermore, we find that CYP4Z1- and CYP4Z2P-3′UTRs increase ERα activity dependent on cyclin-dependent kinase 3 (CDK3). Reporter gene and western blot assays revealed that CYP4Z1- and CYP4Z2P-3′UTRs act as CDK3 ceRNAs. More importantly, the blocking of CYP4Z1- and CYP4Z2P-3′UTRs reversed tamoxifen resistance in MCF-7-TamR cells. Our data demonstrates that the ceRNET between CYP4Z1 and pseudogene CYP4Z2P acts as a sub-ceRNET to promote CDK3 expression in ER-positive breast cancer and is a potential therapeutic target for treatment of tamoxifen-resistant breast cancer. Highlights: A new critical role of ceRNAs in ER + breast cancer is proposed. We examine the relationship of CYP4Z2P, CYP4Z1 and CDK3 in breast cancer. The roles of CYP4Z2P and CYP4Z1 in TAM resistance were further studied. The novel mechanism provides new insights for TAM resistance.